2017
DOI: 10.4236/ojn.2017.76048
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Uncertainty about Infants’ Hospitalization for Acute Childhood Illness: A Qualitative Study

Abstract: Mothers often express intense stress and uncertainty when their children develop acute childhood illnesses and it is important for healthcare professionals to consider maternal uncertainty when providing support for mothers. This study aimed to examine maternal uncertainty about children's hospitalization due to acute childhood illnesses. We recruited 15 Japanese mothers of children aged 1 -12 months who had been hospitalized for the first time due to acute childhood illnesses, and conducted unstructured inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Influencing factors identified in our findings include these uncertainties which led either to parents’ repeated help seeking or to delay in seeking help. Previous parental research identified all the forms of uncertainty identified here (34-36). Uncertainty led HPs to provide safety netting advice, originally conceived, as also reported here, as a way to manage the clinical risk associated with uncertainties around the diagnosis or anticipated illness trajectory(37).…”
Section: Discussionmentioning
confidence: 90%
“…Influencing factors identified in our findings include these uncertainties which led either to parents’ repeated help seeking or to delay in seeking help. Previous parental research identified all the forms of uncertainty identified here (34-36). Uncertainty led HPs to provide safety netting advice, originally conceived, as also reported here, as a way to manage the clinical risk associated with uncertainties around the diagnosis or anticipated illness trajectory(37).…”
Section: Discussionmentioning
confidence: 90%
“…The majority of the included articles were reported from North America, 18 from the USA,2 5 8–10 20–32 3 from Canada11 33 34 and 2 from Mexico 35 36. Of the remaining, six studies were reported from Europe,37–42 two from Asia,13 43 one from Australia6 and one from New Zealand 12…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies used empirical research to develop classifications, of which 12 used a qualitative methodology,5 11 25 27 29 30 33 34 37 39 42 43 2 used quantitative methodology10 22 and 1 used a mixed-methods approach 36. From the mixed-method study, only the qualitative component which pertained to classification development was considered.…”
Section: Resultsmentioning
confidence: 99%
“…The first author conducted open-ended interviews with fifteen mothers of hospitalized children with ACI individually and clarified their uncertainty [12]. The codes in this interview data were replaced with questions.…”
Section: Phase 1: Interviewsmentioning
confidence: 99%
“…Acute childhood illness, in contrast to chronic illness, shows significant changes in symptoms and recovery is expected. We clarified that parents who have a child with ACI felt uncertainty, which composed different from those with chronically ill children [12].…”
mentioning
confidence: 99%